ANALISIPENGARUH SUMBERDAYA ORGANISASI, KEWIRAUSAHAAN, TEKNOLOGI DAN FOREX RATE TERHADAP KINERJA EKSPOR INDUSTRI TEKSTIL DAN PRODUK TEKSTIL (TPT) INDONESIA - Dadim Sinaga (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2008)
This research studies the influence of company resources (organization, enterprenuership, technology) and forex rate perception on export performance of textile industry and textile product in Indonesia. The objective is to examine 60 industrial companies of TPT in Banten (West Java) and DKI Jakarta. The result of the research indicates that, simultaneously, the independent variables (company resources and Forex rate) can predict 63.4 % of probability the dependent variable, and the rest of 36.4 % is predicted by other factors not included in this research. Partially, the resources in technology and organization cannot predict export performance probability, because the regression model of those variables are not significant. However, entreprenuership and perception regarding forex rate can predict export performance probability. This research is expected to benefit TPT industry for improving the global market competitiveness, and also company resources and forex rate researchers, regarding to the theory development and manufacturing company competitiveness in global market.Keywords: Resource- based view, forex , Textile and export performance